Healthy Living: What Are Medicines? Word Search - Karla P. Shelnutt (EDIS)
FCS-8855, a 1-page handout by Karla P. Shelnutt, is a word search using words that relate to medicines. Published by the UF Department of Family Youth and Community Sciences, June 2008.